Individuals with current suicidal ideation demonstrate implicit "fearlessness of death". (June 2016) - Hussey, I.; Barnes-Holmes, D.; Booth, R.
Abstract: Background and objectives: Suicidal behaviour has proved to be difficult to predict, due in part to the particular limitations of introspection within suicidality. In an effort to overcome this, recent research has demonstrated the utility of indirect measures of "implicit" attitudes within the study of suicidality. However, research to date has focused predominantly on implicit self-evaluations and self-death associations. No work has examined implicit evaluations of death, despite the theoretical importance of such evaluations; "fearlessness of death" is central to both the Interpersonal Theory of Suicide and the Integrated Motivational-Volitional model of suicide.. Methods: Twenty-three psychiatric patients with current suicidal ideation and twenty-five normative university students completed two versions of the Implicit Relational Assessment Procedure (IRAP) that targeted evaluations of death. One task specified personal death (i.e., was self-focused) and the other targeted death in the abstract. Results: Self-focused evaluations of death reliably distinguished between the two groups, correctly classifying 74% of cases, but evaluations of death in the abstract did not. The suicidal group produced specific biases indicating a rejection of the negativity of death. Results are consistent with the definition of suicidality as involving a self-focused wish to die.. Limitations: For ethical reason, suicidal behaviours were not assessed in the normative group. Groups were therefore not mutually exclusive. This may have decreased the specificity of the IRAP. Conclusions: Suicidal ideation is associated with an implicit "fearlessness of death". The utility of implicit death-evaluations should therefore be considered alongside self-evaluations and self-death associations in the future.. Highlights: Implicit measures have shown utility over self reports in predicting suicidality. Research to date focused on self-evaluations and self-death associations. A measure of death-evaluations was shown to also have concurrent validity. Suicidal ideation was associated with a lack of negativity towards personal death. Implicit Relational Assessment Procedure shown to have utility within suicidality.